The Influence of Interpersonal Communication and Educational Background on the Headmaster’s Professionalism of PAUD - Diantri Utami; Raihana Raihana; Ida Windi Wahyuni (Institut Agama Islam Negeri Langsa, 2020)
The professionalism headmaster of PAUD strongly influences the quality of PAUD institution. The low competence professionalism headmaster of PAUD is the leading cause of the low quality of education, including the headmaster of PAUD with limited insights regarding early childhood education, lack of communication with colleagues has an impact on motivation and morale found in the field. This research is a quantitative study with multiple regression analysis. This study aims to determine the effect of interpersonal communication and educational background on the professionalism headmaster of PAUD in Indragiri Hulu Regency. Data obtained from the results of the questionnaire distribution of the three variables which were analyzed by multiple regression analysis. The results showed that there was no significant influence between interpersonal communication and educational background on the professionalism headmaster of PAUD in Indragiri Hulu Regency. This is supported by the calculation of the significance test, where the results obtained by the value of Fcount = 0.09, which is smaller than the value of Ftable= 3.13. From the results of the study it can be concluded that the professionalism headmaster of PAUD cannot be separated from the element of educational background because the higher the level and suitability of the department, the more professional workers will be. Likewise, being professionalism depends on controlling the environment through communication.